2011
DOI: 10.1111/j.1743-6109.2010.02120.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Psychological and Sexual Outcomes of Severe Penile Hypospadias Repair

Abstract: Introduction Hypospadias is the most common penis malformation, and there exist a variety of surgical approaches used to correct the abnormal position of the meatus. Although the long-term outcomes of surgery are considered important for psychosexual development, only a few attempts have been made to evaluate patient satisfaction. Aim The aim of our study was to evaluate surgical results and psychosocial adaptations in a homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…No association was found between ejaculatory function, insensitivity of the glans, and orgasmic function. Also, our present patients reached sexual milestones at a similar age as patients with a two‐staged repairs and Dutch adolescents aged 12–24 years .…”
Section: Discussionsupporting
confidence: 73%
“…No association was found between ejaculatory function, insensitivity of the glans, and orgasmic function. Also, our present patients reached sexual milestones at a similar age as patients with a two‐staged repairs and Dutch adolescents aged 12–24 years .…”
Section: Discussionsupporting
confidence: 73%
“…Outcomes are variable and difficult to interpret due to important discrepancies in pre-operative patient characteristics, operative techniques, follow-up duration and the surgeon's outcome perception [5,6]. Also, there is paucity of reports considering the patient's quality of life and perception of the repair, which should ultimately drive management [7].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations about hypospadias suggested that the surgical repair of hypospadias may adversely affect psychosocial and sexual development . However, more recently published studies indicated that patients with corrected hypospadias may show a psychosexual development that is similar to healthy persons if they receive appropriate medical and psychological treatment and mentoring .…”
Section: Introductionmentioning
confidence: 99%